TECHNIQUES FOR IMPROVING THE EFFECTIVENESS OF EDUCATIONAL AND COGNITIVE ACTIVITIES - Najimova Aysara Duysenbaevna (Web of Journals Publishing, 2025)
The need to study this issue is driven by the need to improve the effectiveness of the educational process and the motivational involvement of students through the use of innovative information and communication technologies.
Keywords: Information and communication technologies, teacher, educational process, innovative technologies, educational activities.